Identification of genes potentially involved in solute stress response in Sphingomonas wittichii RW1 by transposon mutant recovery - Coronado, Edith; Roggo, Clémence; van der Meer, Jan R. (Frontiers in Microbiology, 2014)
The term water stress refers to the effects of low water availability on microbial growth and physiology. Water availability has been proposed as a major constraint for the use of microorganisms in contaminated sites with the purpose of bioremediation. Sphingomonas wittichii RW1 is a bacterium capable of degrading the xenobiotic compounds dibenzofuran and dibenzo-p-dioxin, and has potential to be used for targeted bioremediation. The aim of the current work was to identify genes implicated in water stress in RW1 by means of transposon mutagenesis and mutant growth experiments. Conditions of low water potential were mimicked by adding NaCl to the growth media. Three different mutant selection or separation method were tested, which, however recovered different mutants. Recovered transposon mutants with poorer growth under salt-induced water stress carried insertions in genes involved in proline and glutamate biosynthesis, and further in a gene putatively involved in aromatic compound catabolism. Transposon mutants growing poorer on medium with lowered water potential also included ones that had insertions in genes involved in more general functions such as transcriptional regulation, elongation factor, cell division protein, RNA polymerase β or an aconitase.